Analisis Partisipasi Masyarakat dalam Pengembangan Objek Wisata Tubing Lazy River di Desa Penarungan Kecamatan Mengwi, Kabupaten Badung - Saputra, Putu Sandi; Dewi, Nyoman Diah Utari; Widnyani, Ida Ayu Putu Sri (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
The tourism sector influences economic development in Indonesia. This economic development certainly requires the help of the local community. One tourist attraction that has quite a high attraction is The Lazy River in Penarungan Village, Mengwi Subdistrict, Bandung Regency. Therefore, this research is aimed analyzing community participation in planning, management, and utilization stages as well identifying supporting and inhibiting factors for community participation. This research is qualitative research with data collection techniques through observation and interviews. From the results of observations and interviews, it can be concluded that the Lazy River Tubing tourist attraction has its own charm and is suitable as a family-friendly water game with calm water flow and a depth that is safe for various groups. There are many forms of community participation in Penarungan Village which can be seen from community participation in promoting the existence and pride of Lazy River Tubing, both spontaneously and managed.  The supporting factors for community participation are social factor and skills. Then the inhibiting factor is that individuals busy bacgrounds vary in taking the time to participate.